Behavioral Approach Group Counseling to Improve Time Management - Shelsiyanti; Nabila Kurnia Dewi; Syadiva Nugrahaeningtyas; Umi Farchatun; Diani Luthfi Afifah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This writing aims to overcome time management problems experienced by students. This paper applies group counseling services with a behavioral approach that aims to change the behavior of students who initially still apply poor time management in their daily lives to become individuals who can apply better time management in their daily lives or be more disciplined. The provision of counseling services was attended by seven group members. Service delivery lasts for approximately one week. Service delivery is divided into three stages, namely the initial stage of identifying the problems experienced by the counselee, the second stage of the counselor explaining the strategies that can be carried out in consultation, and the third stage of the counselee is asked to apply the strategies that have been agreed upon during consultation, the final stage of this activity is the provision of outcome evaluation and process evaluation which aims to measure whether the counselee has changed in time management.